Pengembangan Sistem Manajemen Mutu Lembaga Pelatihan Kerja Wajo Intelektual Mandiri - Burhanuddin Burhanuddin; Mastang Mastang (Journal of Management and Social Sciences, 2024)
In the era of globalization, competition between companies is increasing in achieving excellence. So companies that have competitive advantages will be able to survive in the competition. Apart from that, with conditions like this, every company is required to survive and have the ability to compete in order to face this competitive climate. Quality of service towards customer satisfaction is one of the factors that plays a very important role in the survival of a company, because this will make the company bigger and able to win every business battle. Therefore, every company tries to ensure that customers are satisfied and trust the company so that it has the potential to provide benefits to the company in the long term. In this research the author uses a descriptive approach in that the research is only descriptive, namely to find out or describe the reality of the events being studied so that it makes it easier for the author to obtain objective data in order to know and understand the development of the Quality Management System at LPK Wajo Intelektual Mandiri. Quality Management System LPK WIM is implemented based on the Plan, Do, Check, Action (PDCA) process which consists of planning steps, plan implementation, checking the results of plan implementation, and corrective action on the results obtained which basically uses Management functions in their implementation based on management achieving quality of both products and services. The implementation of a system formed by the internal LPK Wajo Intelektual Mandiri will certainly have a positive impact on the company, namely improving and guaranteeing the quality of the products or services produced so that in the end it will increase the level of customer satisfaction with the products or services provided.